Pengaruh Sosialisasi Perpajakan, Pengetahuan Perpajakan dan Perhitungan Tarif Pajak pada Kepatuhan Pajak Mahasiswa Pelaku UMKM - Suardana, Komang Putra; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p11, 2020)
The purpose of this study is to study the interaction of tax socialization, tax knowledge, and calculation of tax rates at the level of tax collection of students as SMEs. This research was conducted at the Accounting Study Program of the Faculty of Economics and Business, Udayana University, using a saturated sample. Where the number of samples in this study were 30 people, namely the entire population of accounting studies program students in 2016 and 2017 who have a business producing samples. The sample selection method uses a purposive sampling technique. The analysis technique used is Multiple Linear Regression Analysis. The results found that taxation socialization, tax knowledge, and calculation of tax rates at the level of tax participation of students as SMEs. Keywords: Socialization; Knowledge; Rates;  Tax Compliance.